2016
DOI: 10.1542/peds.2016-1309
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Infections in the First 2 Years of Life

Abstract: BACKGROUND AND OBJECTIVES: Rhinoviruses frequently cause respiratory infections in young children. We aimed to establish the burden of acute respiratory infections caused by rhinovirus during the first 2 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 29 publications
6
61
2
Order By: Relevance
“…This finding could be explained by the genetic factors described in both genders. 20 Despite the fact that RSV A/B is frequent worldwide and its distribution is consistent with a variety of reports in both developing and developed countries, RV has been increasingly reported by previous studies [21][22][23] and was the most frequently detected pathogen in the present study. Its high prevalence makes its infection more serious.…”
supporting
confidence: 91%
“…This finding could be explained by the genetic factors described in both genders. 20 Despite the fact that RSV A/B is frequent worldwide and its distribution is consistent with a variety of reports in both developing and developed countries, RV has been increasingly reported by previous studies [21][22][23] and was the most frequently detected pathogen in the present study. Its high prevalence makes its infection more serious.…”
supporting
confidence: 91%
“…As part of the STEPS study, 923 infants were enrolled in a follow-up for ARIs from birth to age 24 months 1. The details of the study design, setting, subjects, testing and analysis may be found in the online supplement.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcomes were (1) the rate of LRTIs during age 2–24 months and (2) recurrent wheezing by age 24 months. An ARI was defined as the presence of rhinitis or cough (with or without fever or wheezing) documented in the symptom diary by the parents, or as any ARI diagnosed by a physician 1. The LRTIs (eg, bronchiolitis, pneumonia) were diagnosed by physicians.…”
Section: Methodsmentioning
confidence: 99%
“…Most infections cause common cold symptoms. 30 The prevalence of RV-induced bronchiolitis/wheezing is age dependent. In children hospitalized for lower respiratory tract illness, RSV is detected most often until about 12 months of age, and RV is most common in older children.…”
Section: Virus Characteristics Rvsmentioning
confidence: 99%